The impact of self-directed learning on employability: Insights from construction and architecture students in Vietnam - Vo, Anh Tuan; Nguyen , Chi Doan Hanh (Journal of Finance - Marketing Research, 2025)
This study examines the influence of self-directed learning (SDL) on the employability of architecture and construction students in Vietnam. Using data from 463 participants and Structural Equation Modeling (SEM), it analyzes four SDL dimensions: learning motivation, self-management, cooperative learning, and information quality. Results show that learning motivation, self-management, and especially cooperative learning significantly enhance employability. However, information quality does not exhibit a direct effect. The study introduces Expectations from Self (EFS) reflecting psychological capital as a new variable. EFS positively moderates the impact of cooperative learning but unexpectedly weakens the influence of information quality on employability. These findings suggest that students with higher self-expectations benefit more from collaborative learning, while those with lower EFS rely more on information quality. The study contributes to employability theory by integrating EFS and underscores the importance of embedding SDL and personalized support into curriculum design to better prepare graduates for complex labor market demands.